2019
DOI: 10.1159/000503063
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Dietary Avoidance among Individuals with Hidradenitis Suppurativa

Abstract: Background: People with hidradenitis suppurativa (HS) are interested in dietary alterations to manage the condition. However, there are few data on the prevalence of this or the impact on HS activity. The objective of this study was to investigate the prevalence and impact of dietary alterations made by people with HS. Methods: A cross-sectional survey was sent to people with HS through multiple sources. Participants reported food alterations in the prior 6 months. ­Results: Overall, 242 complete surveys were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 29 publications
(34 reference statements)
4
24
0
Order By: Relevance
“…A prior survey study of 242 participants reported that 75.6% of HS patients have practiced dietary alterations, with 30.9% reporting that HS was “much better” after implementing dietary changes 8 . In line with findings from this study, our study identified dairy as a commonly reported exacerbating food in HS 8 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A prior survey study of 242 participants reported that 75.6% of HS patients have practiced dietary alterations, with 30.9% reporting that HS was “much better” after implementing dietary changes 8 . In line with findings from this study, our study identified dairy as a commonly reported exacerbating food in HS 8 .…”
Section: Discussionsupporting
confidence: 88%
“…32.6% (n = 237/728) of participants identified exacerbating food; 12.0% (n = 89/744) of participants identified alleviating foods with findings from this study, our study identified dairy as a commonly reported exacerbating food in HS. 8 We also identified sweets, bread/ pasta/rice, and dairy as the most common dietary triggers, supporting prior hypotheses that the Western diet can worsen HS. 1 However, the impact of increasing intake of specific food groups in HS is less studied.…”
supporting
confidence: 79%
“…In conclusion, in agreement with the study of Dempsey et al [1], we underline once again the role of dietary patterns in the management of HS patients, focusing in particular on bioelectrical impedance analysis parameters (PhA) and MD diet adherence as a potential tool in the therapeutic intervention and prognostic evaluation of HS.…”
supporting
confidence: 90%
“…We have read with great interest the article by Dempsey et al [1] (2019) who carried out a cross-sectional survey on dietary alterations made by patients affected by hidradenitis suppurativa (HS). Their study highlights how avoidance of particular foods is a common management strategy attempted by HS patients [1].…”
mentioning
confidence: 99%
“…A significant portion of the participants (30.9%) reported the dietary change made the HS “much better”. In contrast, some participants did note worsening of their HS when dietary changes were made 24 .…”
Section: Pathophysiology and Triggers Of Hsmentioning
confidence: 92%